Penegakan Hukum Tindak Pidana Penimbunan dan Penyalahgunaan Bahan Bakar Minyak Dihubungkan dengan Undang Undang No 22 Tahun 2001 Tentang Minyak dan Gas Bumi - Ilham Maulana; Arinto Nurcahyono (Bandung Conference Series: Law Studies, 2023)
Abtsract. Fuel hoarding and misuse is a serious matter and a problem that must be resolved immediately, this is due to the impact of hoarding and misuse which is bad for people's welfare. Especially if there is news that there will be an increase in fuel prices, the acts of hoarding and misuse of fuel will become more massive. Even though regulations already exist, the punishments that are imposed are clear, namely the sanctions in Article 53 of Law No. 22 of 2001 concerning Oil and Gas has not been able to compensate for the repeated acts of hoarding and misuse of fuel. This study aims to determine law enforcement efforts against the crime of hoarding and misuse of subsidized fuel oil in Indonesia and to find out the criminal policy towards overcoming the misuse of fuel oil associated with Law no. 22 of 2001 concerning Oil and Natural Gas. The research method used is a normative juridical type, with a statutory regulation approach and relying on primary, secondary and tertiary sources of law.The results of this study are efforts to enforce the law against the crime of hoarding and misusing subsidized fuel oil in Indonesia by using two means, namely penal and non-penal means. Regarding penal facilities, it is specifically regulated in Article 55 of Law No. 22 of 2001 and non-penalty efforts include counseling and legal education, supervising and monitoring the distribution of fuel purchases, establishing cooperation with agents and oil retailers so that they do not participate or cooperate in fuel smuggling. as well as conducting patrols just before the news of the increase in fuel prices. Criminal policies against the prevention of misuse of fuel oil are associated with Law No. 22 of 2001 is in the form of application of criminal law (criminal law application), where provisions for criminal prosecution of all types of fuel abuse are regulated starting from Article 51 to Article 55 of the Oil and Gas Law. Articles 51 to 55 in essence are part of the penal effort to realize people's welfare by reducing the number of acts of fuel abuse. Abstrak. Penimbunan dan penyalahgunaan BBM merupakan hal yang serius dan menjadi masalah yang harus segera dituntaskan, hal ini disebabkan oleh dampak dari penimbunan dan penyalahgunaan yang berakibat buruk bagi kesejahteraan masyarakat. Terlebih jika ada kabar akan ada kenaikan harga BBM, maka perbuatan penimbunan dan penyalahgunaan BBM akan semakin massif terjadi. Walaupun regulasi telah ada bahkan dengan jelas dihukuman yang dikenakan yakni sanksi pada Pasal 53 Undang-undang No. 22 Tahun 2001 tentang Minyak dan Gas Bumi belum mampu mengimbangi terulangnya perbuatan penimbunan dan penyalahgunaan BBM. Penelitian ini bertujuan untuk mengetahui upaya penegakan hukum terhadap tindak pidana penimbunan dan penyalahgunaan bahan bakar minyak bersubsidi Indonesia dan untuk mengetahui kebijakan kriminal terhadap penanggulangan penyalahgunaan bahan bakar minyak dikaitkan dengan Undang Undang No. 22 Tahun 2001 Tentang Minyak Dan Gas Bumi. Metode penelitian yang yang digunakan ialah berjenis yuridis normatif, dengan pendekatan peraturan perundang-undangan dan bertumpu pada sumber hukum primer, sekunder dan tersier. Hasil penelitian ini upaya penegakan hukum terhadap tindak pidana penimbunan dan penyalahgunaan bahan bakar minyak bersubsidi di Indonesia ditegakkan dengan dua sarana yakni sarana penal dan non penal. Pada sarana penal, secara spesifik diatur dalam Pasal 55 UU No 22 tahun 2001 dan upaya non penal ialah meliputi penyululuhan dan edukasi hukum, melakukan pengawasan serta memantau distribusi pembelian BBM, menjalin kerjasama dengan para agen maupun pengecer minyak agar tidak ikut atau bekerjasama dalam penyelundupan BBM serta melakukan patroli pada waktu menjelang kabar kenaikan BBM.. Kebijakan kriminal terhadap penanggulangan penyalahgunaan bahan bakar minyak dikaitkan dengan UU No 22 tahun 2001 ialah berbentuk penerapan hukum pidana (criminal law application), dimana ketentuan pemidanaan terhadap semua jenis penyalahgunaan BBM diatur mulai dari Pasal 51 sampai Pasal 55 UU Migas. Pasal 51 sampai Pasal 55 pada hakikatnya adalah bagian dari upaya penal untuk mewujudkan kesejahteraan masyarakat dengan menekan angka tindak penyalahgunaan BBM.